Cover Feature: Ether‐ and Thioether‐Linked Naphthalene‐Based Liquid‐Crystal Dimers: Influence of Chalcogen Linkage and Mesogenic‐Arm Symmetry on the Incidence and Stability of the Twist–Bend Nematic Phase (Chem. Eur. J. 17/2020). Issue 17 (26th February 2020) - Arakawa, Yuki; Ishida, Yuko; Tsuji, Hideto
Abstract : The twist–bend nematic (NTB) phase possessing a chiral helical nanostructure, which results from achiral bent molecules, has attracted considerable attention in liquid crystal (LC) science. This paper presents ether‐ and thioether‐linked naphthalene‐based LC dimers with symmetric and asymmetric mesogenic arms that exhibit the NTB phase, instead of the most common methylene‐linked dimers. The combination of a thioether linker and asymmetric mesogenic arms is highly beneficial for realizing LC materials that exhibit a broad range of NTB phases and glassy NTB states at room temperature. More information can be found in the Full Paper by Y. Arakawa et al. on page 3767 .